2016
DOI: 10.1089/vbz.2015.1921
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Zoonotic and Vector-Borne Infections Among Afghan National Army Recruits in Afghanistan

Abstract: BR exposure was relatively common with a nearly national distribution, whereas geographic distribution for other pathogens aligned roughly with the expected vector distribution. Public health protection measures should include vector control, food safety, and enhanced diagnostics for acute febrile illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…After a long gap, cases were reported again in 2007, 2009, 2010, 2011, 2012, and 2013 [ 48 ] from this HKH region. In Bangladesh, DEN was only reported in the years 2000 and 2001 [ 68 ] and in Afghanistan in the years 2010 and 2011 [ 35 ]. In the HKH region of Myanmar, DEN cases were reported quite early in 1973 and 1974 [ 73 ], but no DEN cases were reported from there after 1980 [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…After a long gap, cases were reported again in 2007, 2009, 2010, 2011, 2012, and 2013 [ 48 ] from this HKH region. In Bangladesh, DEN was only reported in the years 2000 and 2001 [ 68 ] and in Afghanistan in the years 2010 and 2011 [ 35 ]. In the HKH region of Myanmar, DEN cases were reported quite early in 1973 and 1974 [ 73 ], but no DEN cases were reported from there after 1980 [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many VBDs of human and animal health importance are already endemic in Afghanistan. Malaria, leishmaniasis, CCHF, and LSD are the most common human and animal VBDs in Afghanistan; however, dengue virus and some other vital VBDs are also reported in some parts of the country (Adegboye et al, 2017;WHO, 2017;Todd et al, 2016;Samadi et al, 2021;Madadi et al, 2023;Sangary et al, 2023).…”
Section: Effect Of Climate Change On Vbds In Afghanistanmentioning
confidence: 99%
“…They found that climate change, especially temperature and precipitation, affected the occurrence and distribution of these diseases in Afghanistan. Furthermore, Todd et al (2016) tested 809 people for some zoonotic and VBDs in Afghanistan and found that 2.1% of tested persons had antibodies against the dengue virus.…”
Section: Effect Of Climate Change On Vbds In Afghanistanmentioning
confidence: 99%
“…), and even parasitic helminths ( Wuchereria bancrofti , etc.) [ 1 , 2 , 3 ]. Due to the wide geographical distribution of hematophagous arthropods, globally emerging VBDs infect millions of people annually, especially in developing countries, and hence represent a significant threat to human health.…”
Section: Introductionmentioning
confidence: 99%